Students' and Teachers' Perception on Learning English Language From Home at SMK Negeri 2 Parepare - Nurjannah, Nurjannah (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2021)
This research was conducted to determine the perception of students and teachers learning and teaching English from home related to their perceptions about their problems and their perceptions on learning and teaching English from home. This study used a descriptive qualitative design. The populations of this study were students and teachers of SMK Negeri 2 Parepare. Participants consisted of seven student respondents and seven teacher respondents. In addition, data was collected through observation and interviews. The results showed that students perceptions reveal that learning English from home using learning media used by teachers such as Google Classroom and WhatsApp Group makes it difficult for students to understand the material provided, this is because there is no explanation, no face to face and the questions given are not included with the material. The teacher's perception reveals that the learning media used makes it easier for students to see the questions.